Determination of Metric and Meristic Characteristics of Three Luciobarbus Species (Luciobarbus barbulus, Luciobarbus esocinus and Luciobarbus xanthopterus) Living in Özlüce Dam Lake - Düşükcan, Mustafa; Eroğlu, Mücahit; Çoban, Mehmet Zülfü (Turkish Journal of Agriculture - Food Science and Technology, 2022)
In this study, 51 morphometric 8 meristic characteristics of Luciobarbus barbulus (Heckel 1847), Luciobarbus esocinus Heckel 1843 and Luciobarbus xanthopterus Heckel 1843 species living in Özlüce Dam Lake were examined. Maximum, minimum, mean, standard deviation, standard error and coefficients of variation (%) of morphometric characters and their ratios to each other were calculated. In addition, correlation coefficients were calculated with the regression equation of standard height ratios of morphometric measurements, and as a result, strong positive correlations were determined. From the meristic characters, the number of scales in the lateral line and transversal direction, the number of simple and soft rays on the fins, the number of gill spines, the rows and numbers of the pharynx teeth were determined, and the descriptive features of each species were determined.